2018
DOI: 10.1039/c7cy01838j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic conversion of biomass-derived levulinic acid into alcohols over nanoporous Ru catalyst

Abstract: 1,4-pentanediol or monohydric alcohol were achieved with high selectivity from levulinic acid under relatively mild conditions using nanoporous Ru.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…The presence of zeolite HY provides a higher GVL conversion: the remaining GVL at the end of the reaction was higher for run 27 (in the presence of NBP), rather than for run 26, where the total yield to monoalcohols was 88.8 mol %, with a productivity of 510 mmoles•g•Ru −1 •h −1 . Up to now, the best overall [2-BuOH + 2-PeOH] yield reported in the literature amounts to 78.8 mol %, reached for LA hydrogenation in water at 140 °C and 6.0 MPa H2 in the presence of synthesized nanoporous Ruthenium [54]. Now the experimental finding confirms that the adopted acid zeolite HY enhances the subsequent hydrogenation/decarboxylation reaction towards the formation of 2-BuOH and 2-PeOH.…”
Section: Runsupporting
confidence: 53%
See 1 more Smart Citation
“…The presence of zeolite HY provides a higher GVL conversion: the remaining GVL at the end of the reaction was higher for run 27 (in the presence of NBP), rather than for run 26, where the total yield to monoalcohols was 88.8 mol %, with a productivity of 510 mmoles•g•Ru −1 •h −1 . Up to now, the best overall [2-BuOH + 2-PeOH] yield reported in the literature amounts to 78.8 mol %, reached for LA hydrogenation in water at 140 °C and 6.0 MPa H2 in the presence of synthesized nanoporous Ruthenium [54]. Now the experimental finding confirms that the adopted acid zeolite HY enhances the subsequent hydrogenation/decarboxylation reaction towards the formation of 2-BuOH and 2-PeOH.…”
Section: Runsupporting
confidence: 53%
“…Obregón et al [45] reported the GVL hydrogenation, achieving a maximum 2-BuOH yield of 37.3 mol %, working in 2-PrOH, at 250 °C and 4 MPa H2. Lastly, Lv et al [54] have recently used nanoporous Ru for LA hydrogenation in water, reporting the combined production of both 2-BuOH and 2-Pentanol (2-PeOH), the latter derived mainly from 1,4-PDO hydrogenation, with a total [2-BuOH + 2-PeOH] yield of 78.8 mol %, working at 140 °C for 20 h, with 6 MPa H2. Instead, Obregón et al [45] reported the GVL hydrogenation, achieving a maximum 2-BuOH yield of 37.3 mol %, working in 2-PrOH, at 250 • C and 4 MPa H 2 .…”
Section: Methodsmentioning
confidence: 99%
“…reaction toward 1,4-PDO without any deactivation. Lv et al (2018) reported the one-pot aqueous-phase hydrogenation of LA catalyzed by nanoporous ruthenium-based catalysts to obtain at 100 • C under 60 bar H 2 within 6 h reaction time a yield of 74.6 mol% 1,4-PDO, 1.9 mol% 2-MTHF, 4.6 mol% GVL, 10.4 mol% 2-butanol and 5.0 mol% 2-pentanol. At a higher temperature of 140 • C the yields of both 2-butanol and 2pentanol were increased to 63.6 and 15.2 mol%, respectively, with, however, a low yield of 1,4-PDO of 0.9 mol%.…”
Section: Homogeneous Water-soluble Catalytic Complexesmentioning
confidence: 99%
“…140°C) favored the formation of monohydric alcohols, such as 2-butanol. [186] A highly efficient Mo-modified Ru/activated-carbon (Ru-MoO x /AC) catalyst was prepared for the aqueous-phase hydrogenation of LA to PDO in a continuous fix-bed reactor. An excellent yield of PDO (ca.…”
Section: La To Pdomentioning
confidence: 99%